Equivalent mechanical model of resin-coated aramid paper of Nomex honeycomb. (15th February 2023) - Sun, Jiansong; Wang, Yidan; Zhou, Ping; Wang, Mingye; Kang, Renke; Dong, Zhigang
Highlights: Elasticity and failure behaviors of the resin-coated aramid paper are analysed. A novel segmented equivalent mechanical model of the material is proposed. Equivalent mechanical parameters of multi-layer structure are derived theoretically. Proposed model performs well in ultrasonic cutting simulation of Nomex honeycomb. Difficulty of modelling and CPU time of simulation are reduced significantly. Abstract: Nomex honeycomb, as the core part of sandwich structure, has been widely used in the aviation and aerospace industries. Ultrasonic cutting, as a technology that can reduce machining defects, has been highlighted in recent years, but some problems in the cutting process still need to be investigated significantly. Finite element method (FEM) offers an alternative way of in-depth understanding of the problems. However, the multi-layer structure of the Nomex honeycomb cell wall, which is the resin-coated aramid paper, makes it difficult to establish a detailed multi-layered finite element (FE) model at a macro-scale level. Therefore, a novel segmented material mechanical model, which is applicable to the equivalent single-layer model, is proposed based on the analysis of the mechanical behaviour of the multi-layer structure of the resin-coated aramid paper. Moreover, the calculating method of equivalent mechanical parameters of the multi-layer structure are proposed theoretically. The proposed method is first verified by FE models at a micro-scale level in both single-layer and multi-layer approaches. Additionally, simulations and experiments are performed to verify that the proposed method performs well in the simulation of ultrasonic cutting for Nomex honeycomb, and the difficulty of modelling and CPU time of simulation are reduced significantly. Graphical abstract: Image, graphical abstract